Effect of Treatment Modality on the Hypothalamic–Pituitary Function of Patients Treated with Radiation Therapy for Pituitary Adenomas: Hypothalamic Dose and Endocrine Outcomes - Elson, Andrew; Bovi, Joseph; Kaur, Kawaljeet; Maas, Diana; Sinson, Grant; Schultz, Chris (Frontiers in Oncology, 2014)
Background: Both fractionated external beam radiotherapy and single fraction radiosurgery for pituitary adenomas are associated with the risk of hypothalamic–pituitary (HP) axis dysfunction. Objective: To analyze the effect of treatment modality (Linac, TomoTherapy, or gamma knife) on hypothalamic dose and correlate these with HP-axis deficits after radiotherapy. Methods: Radiation plans of patients treated post-operatively for pituitary adenomas using Linac-based 3D-conformal radiotherapy (CRT) (n = 11), TomoTherapy-based intensity modulated radiation therapy (IMRT) (n = 10), or gamma knife stereotactic radiosurgery (n = 12) were retrospectively reviewed. Dose to the hypothalamus was analyzed and post-radiotherapy hormone function including growth hormone, thyroid stimulating hormone, adrenocorticotropic hormone, prolactin, and gonadotropins (follicle stimulating hormone/luteinizing hormone) were assessed. Results: Post-radiation, 13 of 27 (48%) patients eligible for analysis developed at least one new hormone deficit, of which 8 of 11 (72%) occurred in the Linac group, 4 of 8 (50%) occurred in the TomoTherapy group, and 1 of 8 (12.5%) occurred in the gamma knife group. Compared with fractionated techniques, gamma knife showed improved hypothalamic sparing for DMax Hypo and V12Gy. For fractionated modalities, TomoTherapy showed improved dosimetric characteristics over Linac-based treatment with hypothalamic DMean (44.8 vs. 26.8 Gy p = 0.02), DMax (49.8 vs. 39.1 Gy p = 0.04), and V12Gy (100 vs. 76% p = 0.004). Conclusion: Maximal dosimetric avoidance of the hypothalamus was achieved using gamma knife-based radiosurgery followed by TomoTherapy-based IMRT, and Linac-based 3D conformal radiation therapy, respectively.